EXTENSION AND TRAINING ON ANIMAL REPRODUCTIVE HEALTH AND ANIMAL FEED NUTRITION IN PENDEM VILLAGE, NGARIBOYO, MAGETAN - Hidayatik, Nanik; Lamid, Mirni; Hermadi, Herry Agoes; Warsito, Sunaryo Hadi; Al 'Arif, Mohammad Anam; Hestianah, Eka Pramyrtha; Novianti, Arindita Niatazya; Rosyada, Zulfi Nur Amrina; Sabdoningrum, Emy Koestanti (Universitas Airlangga, 2025)
Pendem Village, Ngariboyo District, Magetan Regency is one of the villages that has the potential for cattle farming. However, cattle breeders in Pendem Village have problems, namely the high incidence of repeated mating in females mated through artificial insemination (AI) and the lack of availability of animal feed in the dry season. The solutions offered in this activity are (1) increasing the knowledge of BUMDes Tirto Mulyo Pendem cattle breeders about cattle reproductive disorders and (2) processing agricultural waste as animal feed in Pendem Village. The output target to be achieved is to increase the understanding of breeders regarding the reproduction of beef cattle and how to process it by making haylage and fermenting agricultural waste. The method used to achieve these output targets is through 2 stages, namely counseling and training. Based on the results of the pre- and post-test, it shows that there is an increase in the knowledge and abilities of breeders related to reproduction and processing of feed derived from agricultural waste, detection of estrus in female cattle, reporting on reproductive health disorders in cattle, causes and symptoms of reproductive disorders in female cattle, the importance of vaccination and animal health programs, cleanliness of pens, cleanliness of individual cattle and fermentation of feed shows an increase in participants who are very knowledgeable from around 0% - 15% to around 4% - 20.7%, it is expected to support the productivity of beef cattle in Pendem Village.